2002
DOI: 10.1038/sj.onc.1205222
|View full text |Cite
|
Sign up to set email alerts
|

p8-deficient fibroblasts grow more rapidly and are more resistant to adriamycin-induced apoptosis

Abstract: p8 is a stress-induced DNA-binding protein, biochemically related to the architectural chromatin binding HMG protein family and whose function is presently unknown. We obtained ®broblast from mice lacking p8 and found that p8 is involved in cell growth regulation and in apoptosis. p8 7/7 mouse embryonic ®broblasts (MEFs) grow more rapidly than p8 +/+ MEFs. This might be explained by the higher intracellular level and activity of the Cdk2 and Cdk4 observed in p8 7/7 MEFs, which in turn may result, at least in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 36 publications
2
98
0
1
Order By: Relevance
“…NUPR1 gene expression was strongly induced by cycloheximide, TNFa, dexamethasone, ceramide, staurosporine, or serum starvation in the AR4-2J cells, a rat pancreatic tumor cell (2). NUPR1 was also upregulated upon exposure to the DNA damage agent, adriamycin, in mouse embryonic fibroblasts (MEFs) (4) and to the genotoxic stress-inducing agent, doxorubicin, in breast cancer cells (5).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…NUPR1 gene expression was strongly induced by cycloheximide, TNFa, dexamethasone, ceramide, staurosporine, or serum starvation in the AR4-2J cells, a rat pancreatic tumor cell (2). NUPR1 was also upregulated upon exposure to the DNA damage agent, adriamycin, in mouse embryonic fibroblasts (MEFs) (4) and to the genotoxic stress-inducing agent, doxorubicin, in breast cancer cells (5).…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that NUPR1 increases p53 intracellular amount and transactivation capacity (4,5). Therefore, to examine the involvement of p53 in the regulation of NUPR1 expression, we measured NUPR1 mRNA levels by RT-PCR in seven lung cancer cell lines with wild and mutant p53 phenotype.…”
Section: Inhibition Of Atf4 Leads To Nupr1 Suppressionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that p8 is a cell growth inhibitor that facilitates apoptosis induced in fibroblasts by DNA damage. 10 The process may involve p53.…”
mentioning
confidence: 99%